The Creation Of An Eco-Tourism Site A Case Study Of Pulau Singa Besar. - Abdullah, A.; Abdul Rahman, A.M.; Bahauddin, A; Mohamed, B. (2006)
Ecotourism is the fastest growing form of tourism in Malaysia. It currently makes up about 10% of the country's tourism revenue.